OLIY TA'LIMDA IQTISODIYOT FANINI O‘QITISHNING O'ZIGA XOS XUSUSIYATLARI VA ZAMONAVIY TALABLARI - Djafarova Shaxlo Ahmadaliyevna (TADQIQOTLAR, 2025)
Abstract.          The development of the economics discipline in higher education in Uzbekistan has been rapidly progressing since the 1990s. Teaching economics combines theory and practice, forming students’ economic knowledge, economic culture, behavior, and responsibility.  Modern  requirements  necessitate  the  development  of  students’ economic literacy, entrepreneurial competencies, adaptation to the digital economy, and preparation of labor market-ready specialists.